Knowledge, Attitude and Practices towards Corona Virus Disease 2019 among Allied Health Students: A Case Study at International Paramedical Institute-Maya, Wakiso District. - Ben Joseph Bwanga; Joseph Kiwu (Student's Journal of Health Research, 2022)
Background:  Coronavirus disease 2019 (Covid-19) is a disease caused by a new strain of coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 was first detected as a respiratory illness in December 2019 in Wuhan City, China, and in March 2020, the World Health Organization classified covid-19 as an international pandemic. This study was done to find out the Knowledge, Attitude, and Practices toward COVID-19 amongst Allied Health students of International Paramedical Institute- Maya using interviewer-administered questionnaires Methodology:  The study was cross-sectional and descriptive. The cross-sectional design utilized surveys to generate quantitative data at the time of data collection. It was cross-sectional because data were collected at one point in time without having to follow up with the study participants thus making the method cheap to execute. Qualitative data was collected using closed-ended researcher-administered questionnaires. It was of an advantage to the researcher because it was affordable and suitable for a short time frame. The survey was conducted in January 2022 and it included 384 participants. Results:  Results of the study revealed that the majority of the allied health students had good knowledge, attitude, and practice toward COVID-19. All the parameters considered to assess knowledge, attitude, and practices had a percentage greater than 50%. Conclusion:   Allied health students at International Paramedical Institute were found to have good knowledge, an optimistic attitude, and appropriate preventive practices toward COVID-19.  Recommendations:  The researcher recommends further studies on larger numbers, diverse responders, and at a community level which will allow us to know the KAP towards COVID-19 in a broad perspective and can be an important tool to plan preventive measures.